SARS-CoV-2 Infection and Guillain-Barré Syndrome: A Review on Potential Pathogenic Mechanisms - Shoraka, Shahrzad; Ferreira, Maria Lucia Brito; Mohebbi, Seyed Reza; Ghaemi, Amir (Frontiers in Immunology, 2021)
Since December 2019, the world has been facing an outbreak of a new disease called coronavirus disease 2019 (COVID-19). The COVID-19 pandemic is caused by a novel beta-coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The SARS-CoV-2 infection mainly affects the respiratory system. Recently, there have been some reports of extra-respiratory symptoms such as neurological manifestations in COVID-19. According to the increasing reports of Guillain-Barré syndrome following COVID-19, we mainly focused on SARS-CoV-2 infection and Guillain-Barré syndrome in this review. We tried to explain the possibility of a relationship between SARS-CoV-2 infection and Guillain-Barré syndrome and potential pathogenic mechanisms based on current and past knowledge.